2019
DOI: 10.1002/cnm.3243
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of deformable particles in a Coulter counter

Abstract: In Coulter counters, cells counting and volumetry are achieved by monitoring their electrical print when they flow through a sensing zone. However, the volume measurement may be impaired by the cell dynamics, which may be difficult to control. In this paper, numerical simulations of the dynamics and electrical signature of red blood cells in a Coulter counter are presented, accounting for the deformability of the cells. In particular, a specific numerical pipeline is developed to overcome the challenge of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…The numerical framework used in this work is the YALES2BIO solver (https://imag.umontpellier.fr/ ~yales2bio/), dedicated to the simulation of RBC dynamics under flow and already used in several publications in the recent years [5,6,19,24,45,46]. It is based on a continuum framework both for the fluid and the membrane.…”
Section: B General Fluid-structure Interaction Algorithmmentioning
confidence: 99%
“…The numerical framework used in this work is the YALES2BIO solver (https://imag.umontpellier.fr/ ~yales2bio/), dedicated to the simulation of RBC dynamics under flow and already used in several publications in the recent years [5,6,19,24,45,46]. It is based on a continuum framework both for the fluid and the membrane.…”
Section: B General Fluid-structure Interaction Algorithmmentioning
confidence: 99%
“…Note that in the case of more spherical particles, the problem of rotation‐associated overestimation of the volume disappears. However, small electrical peaks [34,4,14] may be present at the corner of the orifice. The parameters of the scriptR‐based filter could be modified to detect such peaks, as discussed in Section 3.2.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature [10,11], complex pulses shapes are obtained when deformable and aspherical particles flow near the aperture wall, while 'bell‐shaped' signatures are obtained for centered paths. Previously [14], we directly showed that RBCs deform and, most importantly, rotate when flowing near the wall, which induces a peak on the electrical pulse at the exact moment of the flow‐induced rotation. Golibersuch [13] also reported pulses presenting several peaks when the aperture is long enough to allow RBCs to rotate several times in the sensing region.…”
Section: Methodsmentioning
confidence: 99%
“…The fluid velocity is predicted by solving the incompressible Navier-Stokes equations (NSE) that read: where u , p , ρ and μ are the velocity field, pressure field, constant density and constant dynamic viscosity of the fluid, respectively. To this aim, the NSE are discretized on a fixed numerical mesh and solved using the YALES2BIO solver [ 39 ] ( http://imag.umontpellier.fr/~yales2bio/ ), an in-house CFD solver dedicated to the simulation of blood flows in complex geometries at both macroscopic and microscopic scales [ 40 44 ]. The flow solver uses high-order finite-volume non-dissipative numerical methods to solve the NSE on unstructured meshes [ 45 ].…”
Section: Methodsmentioning
confidence: 99%